Post-activation performance enhancement (PAPE) after a single-bout of high-intensity flywheel resistance training - Maroto-Izquierdo, Sergio; Bautista, Iker; Rivera, Fernando (Biology of Sport, 2020)
This study investigated the post-activation performance enhancements (PAPE) induced by a high-intensity single set of accentuated eccentric isoinertial resistance exercise on vertical jump performance. Twenty physically active male university students performed, in randomized counterbalanced order, two different conditioning activities (CA) after a general preestablished warm-up: a conditioning set of 6 maximum repetitions at high intensity (i.e., individualized optimal moment of inertia [0.083 ± 0.03 kg·m-2]) of the flywheel half-squat exercise in the experimental condition, or a set of 6 maximal countermovement jumps (CMJ) instead of the flywheel exercise in the control condition. CMJ height, CMJ concentric peak power and CMJ concentric peak velocity were assessed at baseline (i.e., 3 minutes after the warm-up) and 4, 8, 12, 16 and 20 minutes after the CA in both experimental and control protocols. Only after the experimental protocol were significant gains in vertical jump performance (p < 0.05, ES range 0.10–1.34) at 4, 8, 12, 16 and 20 minutes after the CA observed. In fact, the experimental protocol showed greater (p < 0.05) CMJ height, concentric peak power and concentric peak velocity enhancements compared to the control condition. In conclusion, a single set of high-intensity flywheel training led to PAPE in CMJ performance after 4, 8, 12, 16 and 20 minutes in physically active young men.